Cyclic tensile stimulation enrichment of Schwann cell-laden auxetic hydrogel scaffolds towards peripheral nerve tissue engineering. (October 2020) - Chen, Yi-Wen; Wang, Kan; Ho, Chia-Che; Kao, Chia-Tze; Ng, Hooi Yee; Shie, Ming-You
Abstract: The nervous system in the body is a complex network of nerves and cells that regulates several functions. Neural regeneration is a complex process that involves matrix secretion and remodeling, in which growth factors play a huge role in regulating such processes. Recent studies demonstrated the structures and topography of scaffolds are expected to provide a spectrum of unique biomimetic 3D microenvironments to regulate cell behavior. In this study, we fabricated auxetic scaffolds using fish gelatin methacrylamide and evaluated the effects of cyclic tensile stimulation effects on the neural differentiation capabilities of human Schwann cells. The auxetic hydrogels were found to withstand up to 20% tensile strain without tears, and the hydrogels had lost only about 10% weight after immersed for 14 days. The tensile forces were able to enhance cell viability and proliferation as compared to a static culture. In addition, the secretion of neural regeneration-related proteins was enhanced in the tensile stimulation group. The cell-laden auxetic scaffold with tensile stimulation caused improvement in the nerve growth factor and TRKA receptor expression. This is the first study to combine tensile stimulation with NGF. The initial results showed the positive potential of such conditions being applied in clinical applications. Graphical abstract: Unlabelled Image Highlights: The cell-laden auxetic scaffold with negative Poisson's ratio was fabricated by using the extrusion-based bioprinting strategy. The photocurable fish gelatin-methacryloyl hydrogel exhibited superior degradability, elasticity, and cytocompatibility to support the growth of human Schwann's cells. The proliferation of human Schwann's cells encapsulated in the auxetic scaffold was promoted while applying cyclic tensile forces. The cyclic tensile stimuli enhanced expression of nerve growth factor and tropomyosin receptor kinase A receptor of the cells. The external nerve growth factors elevated the growth and transcription factors levels of the tensile-stimulated cells through PI3K/AKT pathway.